AB1286 Dermoscopic images of telangiectasias and nailfold videocapillaroscopic patterns in systemic sclerosis patients. (23rd January 2014) - Gianpetruzzi, A.R.; Bono, R.; Mondino, C.; Facchiano, A.; Didona, B.; Puddu, P.; De Pità, O.; Colonna, L.; Raskovic, D.; Sulli, A.; Cutolo, M.
Abstract : Background: Systemic sclerosis (SSc) is characterized by progressive microvascular abnormalities that lately may appear as skin telangiectasias (TA). Microangiopathy associated with SSc is typically visualized using nailfold videocapillaroscopy (NVC). Objectives: To describe skin SSc TA distribution through the investigation of altered capillaries using skin dermoscopy (DC) and search possible correlations with NVC SSc patterns ("early", "active" and "late") and clinical status. Methods: Thirty-one female SSc patients (mean age 53.5±29.5 yrs, disease duration 19±18 yrs), diagnosed according to the LeRoy criteria and showing at DC analysis cutaneous-mucous TA, were recruited after informed consent and Ethical Committee approval. Patients were grouped according to diffuse (dSSc) and limited (lSSc) subtypes. We used DC (at 25x and 40x magnifications) to evaluate TA on the face, décolleté, shoulders, back of hands and palms. Qualitative SSc NVC patterns ("early", "active", "late" at 200x magnifications) and specific autoantibodies (Scl70 and ACA) were searched. Patients were classified into subgroups (lSSC/dSSC, Scl70/ACA) and analysed according to modified ROC analysis, scoring 0 or 1 to indicate absence or presence of a feature. Analysis was done using Prism 5 for Windows (graphPad Software, Inc, LA Jolla, CA), with statistical significance set at p≤0.03. Results: Seven-teen SSc patients were found lSSc (17/31, 54.83%; mean disease duration 8.70 yrs) the remaining four-teen were found dSSc (14/31, 45.1% mean disease duration 11.14 yrs). The predominant DC TA patterns observed were "spot" (violet and suffused pink sometimes associated to punctiform vessels) on the hands and "reticular" (alveolar and branched vessels) on the other sites (mainly face). "Spot" DC TA pattern (prevalent in the hands) was found mainly associated with "early"/"active" NVC patterns in lSSc patients (91% vs. 9% "early"/"active" vs "late" NVC pattern, respectively), whereas "reticular" DC TA pattern was found mainly associated with "active"/"late" NVC patterns in dSSc patients, (92% vs 8% "active"/"late" vs "early" NVC pattern, respectively). In addition, TA on the palms appeared as "spot" DC pattern in 15 of 31 patients, including 13in the ACA positive patients (13/20; ROC area 0.7, p=0.03). A DC TA pattern consisting of suffused pink was observed on the palms of 13 patients, including 10 of 11 patients in the anti-Scl-70-positive group (ROC area 0.8, p=0.009). Conclusions: Both DC and NVC are confirmed sensitive techniques describing the progressive skin microvascular changes in SSc patients. DC detects better than NVC, the alterations of horizontal plexus (``reticular" DC pattern) that are mainly evident in advanced SSc disease and due to angiogenesis (``late" NVC pattern). On the contrary, NVC allows the crucial early detection of the skin papillary microvascular damage (SSc NVC "early" pattern: giant capillaries and micro-haemorrhages) that DC may only partially distinguish (especially on the hands). References: Cutolo M al. J Rheumatol. 2000; 27:155–60 LeRoy EC et al. J Rheumatol. 1988;15:202-5. Disclosure of Interest: None Declared